Characterization of normal and mastitic milks using Raman Spectroscopy by application of SERS method - Açıkgöz, G; Coşkun, P; Ergün, Y; Başpinar, N; Kazak, F (Journal of the Hellenic Veterinary Medical Society, 2024)
One of the problems of the dairy industry which causes major economic losses due to reduced milk yield and quality, is "Mastitis". Mastitis is a disease that occurs in the glandular tissue of the mammary gland caused by infectious agents. Since milk and milk derived products are consumed by a large part of the World’s population, the quality of milk becames important. Rapid, non-destructive analysis of the milk by Raman Spectroscopy is of great advantage. In the study, it is aimed to investigate the molecular structures of normal and mastitic milks using Raman spectroscopy and this study is the first study done for this purpose. In the study, the presence or absence of functional groups of the spectra obtained from the milk samples was compared with the reference spectra in other studies. It was observed that the peaks obtained from the biochemical structures of normal and mastitic milks were consistent with the literature. In addition, it was found that the biochemical components of subclinical mastitis and normal milk did not change at the molecular level. It was thought that there was no change at the molecular level as there was no visible deterioration in the milk with subclinical mastitis and the factor caused by the infection in the breast tissue. Keywords: Raman Spectroscopy; SERS method; mastitis; milk